2017
DOI: 10.1186/s12974-017-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid via LPA-receptor 5/protein kinase D-dependent pathways induces a motile and pro-inflammatory microglial phenotype

Abstract: BackgroundExtracellular lysophosphatidic acid (LPA) species transmit signals via six different G protein-coupled receptors (LPAR1–6) and are indispensible for brain development and function of the nervous system. However, under neuroinflammatory conditions or brain damage, LPA levels increase, thereby inducing signaling cascades that counteract brain function. We describe a critical role for 1-oleyl-2-hydroxy-sn-glycero-3-phosphate (termed “LPA” throughout our study) in mediating a motile and pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 123 publications
(121 reference statements)
8
51
0
Order By: Relevance
“…Earlier studies have indicated an ability of LPA to induce p38 phosphorylation in J774 and other cell types, e.g., murine microglia, embryonic carcinoma cells, and rat fibroblasts . In our studies, a role of p38 in the IL‐10 production in LPA/LPS‐stimulated cells was indicated by its abrogation by the p38 inhibitor SB 202190 and also by the analysis of the dynamics of p38 phosphorylation and IL‐10 secretion in LPA and/or LPS‐treated cells.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Earlier studies have indicated an ability of LPA to induce p38 phosphorylation in J774 and other cell types, e.g., murine microglia, embryonic carcinoma cells, and rat fibroblasts . In our studies, a role of p38 in the IL‐10 production in LPA/LPS‐stimulated cells was indicated by its abrogation by the p38 inhibitor SB 202190 and also by the analysis of the dynamics of p38 phosphorylation and IL‐10 secretion in LPA and/or LPS‐treated cells.…”
Section: Discussionsupporting
confidence: 69%
“…Until now, the immunomodulatory role of LPA 5 and LPA 6 has been addressed in few studies only. The pro‐inflammatory responses induced by LPA in microglia, e.g., expression of pro‐inflammatory M1‐type markers and secretion of pro‐inflammatory cytokines, were attenuated by an LPA 5 inhibitor . Inhibition of B‐cell receptor signaling was observed following activation of LPA 5 in murine B cells .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This indicates that LPA 5 signaling is related to neuropathic pain mediated by multiple sclerosis [96]. It was found that intravenous LPA and GGPP (LPA 5 agonists) induced allodynia, but GGPP-induced allodynia did not show up in LPA 5 -KO mice, indicating pain signals in the spinal cord by LPA 5 transfer [94][95][96].…”
Section: Lpar and Neuropathic Painmentioning
confidence: 99%
“…LPA may activate macrophages/microglia via LPAR1 and LPAR3 and promote self-amplification of LPA, increasing microglial migration and pro-inflammatory phenotype through the LPAR5/protein kinase D (PKD) axis. Activation and migration of microglia are associated with demyelination in the spinal cord after injury, and microglia are more involved in the initiation of neuropathic pain (NP) [94,95]. In the cuprizone (CPZ)-induced multiple sclerosis (MS) model, LPA5 signaling mediates pain allergy induced by A-delta fibers and demyelination produced by CPZ.…”
Section: Lpar and Neuropathic Painmentioning
confidence: 99%